2019
DOI: 10.2147/cmar.s216929
|View full text |Cite
|
Sign up to set email alerts
|

<p>Adverse effect of laparoscopic radical hysterectomy depends on tumor size in patients with cervical cancer</p>

Abstract: PurposeThe study aimed to explore the survival outcomes of early-stage cervical cancer (CC) patients treated with laparoscopic/abdominal radical hysterectomy (LRH/ARH).Patients and MethodsWe performed a retrospective analysis involving women who had undergone LRH/ARH for CC in early stage during the 2013–2015 period in West China Second University Hospital. The survival outcomes and potential prognostic factors were evaluated using Kaplan–Meier method and Cox regression analysis, respectively.ResultsA total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Study design Matched 10 (5,11,13,15,16,19,28,30,41,43) 1.49 (1.19-1.88) 0.001 27.5 Fixed effect Retrospective 26 (6-10, 12, 14, 17, 18, 20-27, 29, 31-34, 42, 44-46) 1. (12,13,19,23,24,(27)(28)(29)(30)(31)(32)(33)(34)(42)(43)(44)(45)(46) 1. Small (at least one arm < 90) 18 (5-11, 14-18, 20-22, 25, 26, 41) 0.90 (0.67-1.20)…”
Section: Fixed Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Study design Matched 10 (5,11,13,15,16,19,28,30,41,43) 1.49 (1.19-1.88) 0.001 27.5 Fixed effect Retrospective 26 (6-10, 12, 14, 17, 18, 20-27, 29, 31-34, 42, 44-46) 1. (12,13,19,23,24,(27)(28)(29)(30)(31)(32)(33)(34)(42)(43)(44)(45)(46) 1. Small (at least one arm < 90) 18 (5-11, 14-18, 20-22, 25, 26, 41) 0.90 (0.67-1.20)…”
Section: Fixed Effectmentioning
confidence: 99%
“…Before LACC trial 22 (5-24, 41, 42) 0.89 (0.71-1.11) 0.289 0.0 Fixed effect After LACC trial 14 (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(43)(44)(45)(46) 1. 17 (5, 11, 12, 17, 19, 21, 22, 24-26, 29, 31, 32, 41-43, 45) 1.06 (0.87-1.30) 0.555…”
Section: Published Yearmentioning
confidence: 99%
“…Since the first report in 2018, 8 , 9 more studies 16–18 have focused on the possible adverse effects of LRH on the prognosis of patients with early cervical cancer, and some have recommended ORH for cervical cancer patients. 19 LVSI, tumor size, lymph node metastasis, interstitial infiltration depth, and parametrial infiltration all adversely influence the prognosis of early cervical cancer patients, 20 , 21 and similar results were found in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al 16 also found that at a tumor diameter >4 cm, the overall survival (OS) and progression-free survival (PFS) in a cohort of patients who underwent LRH were significantly shorter than in those who underwent abdominal radical hysterectomy (ARH), and they recommended ARH as the first-line surgical treatment option when the patient’s tumor diameter is >4 cm. Pedone Anchora L et al observed in their study 22 that at a tumor size >20 mm, LRH, compared with ORH, was significantly associated with an increased relapse rate, and they identified tumor size as the primary factor influencing surgical approach selection.…”
Section: Discussionmentioning
confidence: 99%
“…The laparoscopic approach for early cervical cancer has been widely used for more than 20 years since it was rst reported in 1989 [10]. Previous studies of our group indicated that the adverse effect of laparoscopic approach for cervical cancer patients was in uenced by tumor size [11,12]. A multicenter retrospective study just published by our group found the same results with LACC trail in patients with a tumor diameter ≥ 2cm, however, amid the patients with a tumor diameter < 2cm, the laparoscopic radical hysterectomy and abdominal radical hysterectomy groups had similar disease-free survival (HR 0.71, 95% CI 0.24 to 2.16; p=0.59) and overall survival (HR 0.59, 95% CI 0.11 to 3.13; p=0.53) [12].…”
Section: Discussionmentioning
confidence: 99%